2022
DOI: 10.3389/fimmu.2022.937331
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming alternative macrophage polarization by GATM-mediated endogenous creatine synthesis: A potential target for HDM-induced asthma treatment

Abstract: Cellular energy metabolism plays a crucial role in the regulation of macrophage polarization and in the execution of immune functions. A recent study showed that Slc6a8-mediated creatine uptake from exogenous supplementation modulates macrophage polarization, yet little is known about the role of the de novo creatine de novobiosynthesis pathway in macrophage polarization. Here, we observed that glycine amidinotransferase (GATM), the rate-limiting enzyme for creatine synthesis, was upregulated in alternative (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Macrophages are critical in the amplification and effector phase and damage the myelin sheath by phagocytic attack and release of inflammatory mediators such as toxic oxygen radicals, arachidonic acid metabolites, complement, or hydrolases [ 51 ]. Macrophage polarization is accompanied by dramatic changes in L-arginine metabolism [ 52 ]. The third metabolic fate of l -arginine is creatine generation, which acts as a key source of cellular energy reserve, yet little is known about the role of creatine in the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are critical in the amplification and effector phase and damage the myelin sheath by phagocytic attack and release of inflammatory mediators such as toxic oxygen radicals, arachidonic acid metabolites, complement, or hydrolases [ 51 ]. Macrophage polarization is accompanied by dramatic changes in L-arginine metabolism [ 52 ]. The third metabolic fate of l -arginine is creatine generation, which acts as a key source of cellular energy reserve, yet little is known about the role of creatine in the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that glycine amidinotransferase (GATM) was upregulated in M2-polarized macrophages. GATM deletion inhibited the expression of RETNAL and blocked M2 polarization [ 66 ]. Based on these, we speculate that GATM may regulate RETNLA to affect M2 macrophage polarization during H1N1pdms infection.…”
Section: Discussionmentioning
confidence: 99%
“…GATM, the rate-limiting enzyme in creatine synthesis, was found to be upregulated in alternative (M2) polarized macrophages, and its expression was dependent on the transcriptional factor STAT6. Conversely, GATM expression was suppressed in classical polarized (M1) macrophages . Furthermore, GATM was observed to be upregulated in liver metastases, and it was discovered that creatine promotes cancer metastasis through the activation of Smad2/3 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, GATM expression was suppressed in classical polarized (M1) macrophages. 60 Furthermore, GATM was observed to be upregulated in liver metastases, and it was discovered that creatine promotes cancer metastasis through the activation of Smad2/3. 61 Therefore, it is plausible that lactylation at K102 of GATM plays a role in the development of hypertrophic scars through the involvement of creatine and the Smad2/3 pathways.…”
Section: ■ Discussionmentioning
confidence: 99%